2018
DOI: 10.1126/science.aar2009
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up synthesis of multifunctional nanoporous graphene

Abstract: Nanosize pores can turn semimetallic graphene into a semiconductor and, from being impermeable, into the most efficient molecular-sieve membrane. However, scaling the pores down to the nanometer, while fulfilling the tight structural constraints imposed by applications, represents an enormous challenge for present top-down strategies. Here we report a bottom-up method to synthesize nanoporous graphene comprising an ordered array of pores separated by ribbons, which can be tuned down to the 1-nanometer range. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
538
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 499 publications
(567 citation statements)
references
References 59 publications
23
538
0
6
Order By: Relevance
“…On‐surface bottom‐up approaches using chemically designed precursors are regarded as a promising method to produce GNRs with defined edges and widths . Further, lateral fusion of parallelly aligned GNR led to generation of 2D graphene nanoribbon networks (GNNs) . However, it is difficult to efficiently create such sophisticated GNR‐linkage structures, since their formation is based on a stochastic surface reaction that requires close proximity between the precursors on the surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On‐surface bottom‐up approaches using chemically designed precursors are regarded as a promising method to produce GNRs with defined edges and widths . Further, lateral fusion of parallelly aligned GNR led to generation of 2D graphene nanoribbon networks (GNNs) . However, it is difficult to efficiently create such sophisticated GNR‐linkage structures, since their formation is based on a stochastic surface reaction that requires close proximity between the precursors on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…[9] However,f ully p-conjugated 2D structures attractm uch attention, since they can provide conducting carbon-based nanostructures with holey structures highly suitable for various electronic applications.U tilization of large fully p-conjugated building blocks such as GNRs, which are 1D carbon-based nanowires, is becoming ap romising approacht op roduce extended 2D pconjugated systems via surface assistedl ateral fusion of GNR chains. [10,11] On-surface bottom-up approaches using chemically designed precursors are regarded as ap romising methodt o produce GNRs with defined edges and widths. [12] Further,l ateral fusion of parallellya ligned GNR led to generation of 2D graphene nanoribbon networks (GNNs).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, modification of the precursor molecule 1 enables tuning the electronic structure of the ribbons. For instance, molecule 10 with an added phenyl substituent in molecule 1 is designed to fabricate yield (shown in Figure a) and, experimental STS spectra has demonstrated that its band gap is 1.0 eV (Figure b), which is smaller than pristine 7‐ AGNR . 7‐ AGNRs with −CN functional groups edge modification induce a downshift on the ribbon bands of ∼0.3 eV per −CN added (Figure c and Figure d) .…”
Section: Tuning the Electronic Propertiesmentioning
confidence: 99%
“… Edge‐modified armchair GNRs. (a) The high‐resolution images of 7‐ phenyl‐GNRs by using a CO‐functionalized tip in constant‐height mode . (b) The corresponding dI/dV spectra of 7‐ phenyl‐GNRs .…”
Section: Tuning the Electronic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation